Pengaruh Kepribadian Islami, Akses Informasi, Dan Inovasi Bisnis Terhadap Kinerja Bisnis (Studi Usaha Penyulingan Minyak Daun Cengkeh Kabupaten Sinjai) - Fatha Isman, Ainul; Rusdi, Wahyudi (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2022)
Entrepreneurship is one of the drivers of Indonesian economy, is needed to improve the performance of the business. Many aspects can affect the performance of a business so that it can develop. The purpose of this study is to analyze the influence of Islamic personality, information access, and business innovation on business performance in the clove daub oil refining business. The research methodology used is quantitative research with a descriptive analysis approach. The results of this study show that Islamic personality does not have a positive effect on the business performance of clove leaf oil refining business. Meanwhile, information access and business innovation have a significant effect on the business performance of clove leaf oil refining business. Information access is the most influential aspect of the business performance of clove leaf oil refining business, especially in the current era of digital development. The implications of this research are to develop micro, small and medium enterprises and to support the progress of entrepreneurship, especially in empowering regional potential.